Роль та особливості залучення експерта-психіатра стороною захисту в судовому процесі: підвищення об’єктивності та захист прав обвинувачених - Макарова, О. П.; Makarova, O. P. (Право.ua. - 2024. - № 1. - С. 128-134, 2024)
Розглянуто правові стандарти та етичні норми, які регулюють залучення експерта - психіатра стороною захисту. Судово-психіатрична експертиза обвинуваченого підпадає під чисельні правові та етичні норми, спрямовані на забезпечення об’єктивності та захисту прав людини, до яких належать: незалежність та об’єктивність; дотримання професійних стандартів; конфіденційність та приватність; відповідність юридичним процедурам; інформована згода та права обвинуваченого; відсутність обвинуваченого; співпраця з органами слідства та дізнання. Підкреслено, що залучення експерта-психіатра стосовно захисту є важливим елементом для створення справедливого та етичного судового процесу, спрямованого на захист прав обвинуваченого.

The article is devoted to the analysis of the role and features with an emphasis on increasing objectivity and protecting the rights of the accused. Key aspects of this process include: examination of accusations; analysis of testimony and testimony; psychological examination before the court session; refutation of expert opinions by the prosecution; formation of a positive (as much as possible) image of the accused; ethical review and conference defense. The task of the article was to reveal the key aspects of the interaction between the legal and medical environments, with the aim of improving the judicial process. The legal standards and ethical norms governing the involvement of an expert - a psychiatrist by the defense side are considered. Forensic psychiatric examination of the accused is subject to numerous legal and ethical norms aimed at ensuring objectivity and protection of human rights, which include: independence and objectivity; compliance with professional standards; confidentiality and privacy; compliance with legal procedures; informed consent and rights of the accused; absence of the accused; cooperation with investigation and inquiry bodies. Emphasis is placed on the need for psychiatrists to observe high ethical standards in the context of forensic examinations. The issue of objectivity of expert opinions and avoidance of conflict of interests is considered. The importance of providing objective and responsible conclusions by an expert - a psychiatrist, which serves as the basis for court decisions. The important contribution of the expert psychiatrist to the judicial process is highlighted, contributing to a balanced and objective consideration of the case. Emphasis is placed on improving legal and medical cooperation, the need for mutual understanding and effective communication is emphasized for the optimal use of expert opinions and the achievement of fair and objective court decisions. These key aspects include: communication and understanding of needs; pooling of expert knowledge; joint trainings and seminars; creation of discussion mechanisms; ensuring confidentiality and impartiality. It was concluded that the involvement of an expert - a psychiatrist in relation to the defense is an important element for creating a fair and ethical trial aimed at protecting the rights of the accused.

Рассмотрены правовые стандарты и этические нормы, регулирующие привлечение эксперта – психиатра стороной защиты. Судебно-психиатрическая экспертиза обвиняемого подпадает под многочисленные правовые и нравственные нормы, направленные на обеспечение объективности и защиты прав человека, к которым относятся: независимость и объективность; соблюдение профессиональных стандартов; конфиденциальность и приватность; соответствие юридическим процедурам; информированное согласие и права обвиняемого; отсутствие обвиняемого; сотрудничество с органами следствия и дознания. Подчеркнуто, что привлечение эксперта-психиатра по защите является важным элементом для создания справедливого и нравственного судебного процесса, направленного на защиту прав обвиняемого.
The role and characteristics of involving an expert - a psychiatrist by the defense party in the trial: increasing objectivity and protecting the rights of the accused
Keywords: судово-психіатрична експертиза; захист обвинуваченого; експерт-психіатр; кримінальне провадження; forensic psychiatric examination; defense of the accused; expert psychiatrist; criminal proceedings; судебно-психиатрическая экспертиза; защита обвиняемого; эксперт-психиатр; уголовное производство